Digitalization Of Sociopreneurship In Efforts Of Business Development And Optimization Of Workforce Empowerment - Hasna Larasati (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2023)
Sociopreneurship are one of the important goals in the Sustainable Development Goals (SGDs) related to overcoming poverty. Factors that influence the existence of poverty is the lack of jobs which causes many unemployed in Indonesia. In efforts to empower the workforce in overcoming unemployment, what really needs to be considered is the disabled workforce. Disabled workers have several obstacles and challenges in adapting to the world of work. These obstacles and challenges relate to the ability and knowledge of information technology. Information technology is currently very influential in the economy in Indonesia. Several industries, companies and businesses are digitizing with the aim of developing business in the current digital era. However, there are also businesses that still haven't implemented digitization. The low percentage of digitization implementation is a major challenge in growing and adapting to digital technology. Limitations and accessibility in studying, understanding and applying digitalization abilities and knowledge, support is needed in efforts to optimize technology in empowering disabled workers. This study aims to describe a digitalized business model that is appropriate by identifying the business model, internal factors and external factors, digitalization strategies in efforts to develop sociopreneurship businesses and strategies to increase information technology capabilities and knowledge for workers with disabilities in optimizing workforce empowerment in adapting to digital era in industry.